PENERAPAN PEMBELAJARAN BERBASIS LABORATORIUM VIRTUAL BERBANTUKAN LIVEWORKSHEETS PADA MATERI ALAT OPTIK UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS XI SMAN 16 PEKANBARU - Safina Salma Ramadini; M.Nor M.Nor; Dedi Irawan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : Students science process skills are aspects that must be trained through hands-on practicals. In fact, the lack of adequate practicum facilities in the physics laboratory causes students to rarely do practicums so that students' scientific process skills do not develop. Along with the rapid development of technology, there has been an innovation in the form of a virtual laboratory as an alternative solution for schools that lack practical tools and materials. This study aims to determine the differences in students' science process skills between classes that apply virtual laboratory-based learning assisted by live worksheets and classes that apply conventional learning. The type of research used is Quasi-Experiment with Post-test Only design, Non-Equivalent Control Group Design. The data collection instrument was in the form of post-test questions (scientific process skills test). Data were analyzed using descriptive analysis and inferential analysis. The results of the descriptive analysis showed that the students' science process skills in the experimental class were higher than the control class. This was shown in the experimental class, the percentage of students' average KPS scores reached 78.76% and the control class 66.59%. From the results of data analysis, it can be concluded that students' science process skills between classes with virtual laboratory-based learning assisted by live worksheets are better than classes with conventional learning on optical instrument material in class XI SMAN 16 Pekanbaru.Keywords: Optical Instrument, Science Process Skills, Virtual Laboratory, Liveworksheets